Effects of groove parameters on space constraint of narrow gap laser-arc hybrid welding. (June 2018) - Meng, Yunfei; Li, Geng; Gao, Ming; Zeng, Xiaoyan
Highlights: Obvious space constraint effect (SCE) is found in narrow gap laser-arc hybrid welding. The SCE varies with different rectangle groove width and Y-shape groove angle. The melting energy increment (ψ) is adopted to quantitatively calculate the SCE. The rectangle groove is better groove type than Y-shape groove with higher ψ, up to 30%. Abstract: Obvious space constraint effect (SCE) related to energy transfer was found in narrow gap laser-arc hybrid welding (NGHW). It was significantly affected by changing the width of rectangle groove (WG ) and the angle of Y-shape groove (αG ), and the central crack and sidewall notch occurred on weld cross-section when WG  ≤ 4 mm or αG  ≤ 60°. The SCE was quantitatively characterized by the dimensionless parameter of melting energy increment (ψ), which is the increment of melting efficiency of NGHW to the hybrid welding without narrow gap. The larger the ψ, the stronger the SCE. The ψ of rectangle groove was up to 30% when the WG was at 6 mm, while the maximum of the ψ of Y-shape groove was only 7% when the αG was at 60°. According to the calculated ψ and the defect occurring tendency, the optimized groove of NGHW was confirmed as the rectangle groove with 6 mm-width, and was verified by a 25 mm-thick joint. Besides, the effects of SCE on the energy transfer in narrow gap were discussed according to the behaviors of arc column and laser-induced plasma.